A5 6 Winds of Arrakis - Taylor, Josh; Edward Greathead; Jaspreet Rai (Physics Special Topics, 2024)
In the book series ’Dune’, the planet Arrakis is home to major sandstorms that are amplified by the planet’s rotational motion, these being referred to as ’Coriolis storms’. We investigated the magnitude of the Coriolis force and hence the total vertical pressure gradient force necessary to produce storms of this magnitude. It was found that a total Coriolis force of Fc ≈ 0.02 ms-2 , and hence a vertical pressure gradient force of ≈ -0.026 ms-2 was required to produce wind speeds that facilitate these weather conditions.